Penerapan Metode Bermain Kolase Dari Biji-Bijian Terhadap Perkembangan Sosial Emosional Anak Usia 5-6 Tahun di TK Negeri 1 Muara Ancalong - Gusaimah Aspiah; Mumpuniarti Mumpuniarti (Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to examine: (1) the condition of social-emotional development of 5–6-year-old children at TK Negeri 1 Muara Ancalong before the implementation of the collage play method; (2) the process of implementing collage play activities using grains in classroom learning; (3) the influence of collage play activities on the social-emotional development of young children; and (4) the supporting and inhibiting factors in implementing the collage play method to enhance the social-emotional development of early childhood. The focus of this research is how the collage play method can serve as an effective approach to foster children's social and emotional aspects optimally in an early childhood education setting. This research employed a qualitative approach with descriptive methods. Data were collected through observations of 19 children aged 5–6 years, interviews with the class teacher of group B II and the principal, as well as documentation related to the learning process. The research was conducted at TK Negeri 1 Muara Ancalong. The data were analyzed descriptively to describe the conditions and processes that occurred during the implementation of the collage play method. The results show that the collage play method can enhance children's social-emotional development. The planning and implementation of activities were systematically designed and carried out by the teacher. The children showed improvements in several aspects, such as curiosity, emotional regulation, and social engagement. Additionally, there were supporting factors such as the availability of learning materials and teacher involvement, as well as inhibiting factors such as time constraints and the need for individualized attention. By maximizing the supporting factors and minimizing the obstacles, the collage play method proved to be an effective alternative for developing the social-emotional aspects of early childhood.